Coping : the Psychology of What Works. - Snyder, C. R. (Oxford University Press, 1999)
Most people take the process of coping for granted as they go about their daily activities. In many ways, coping is like breathing, an automatic process requiring no apparent effort. However, when people face truly threatening events--what psychologists call stressors--they become acutely aware of the coping process and respond by consciously applying their day-to-day coping skills. Coping is a fundamental psychological process, and people's skills are commensurately sophisticated. This volume builds on people's strengths and emphasizes their role as positive copers. It features techniques for.